1994
DOI: 10.1177/096120339400300604
|View full text |Cite
|
Sign up to set email alerts
|

Autoimmunity and Heavy Metals

Abstract: This brief review is focused on those heavy metals (cadmium, gold and mercury) that have strong associations with autoimmunity. Cadmium treatment of rats and mice results in autoimmune responses that vary with species and inbred strain of animals. However, there is no solid evidence demonstrating that the renal pathology observed in humans exposed to cadmium has an autoimmune pathogenesis. More clear-cut are the autoimmune effects of preparations containing gold salts, that have been widely used in the treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
29
0
1

Year Published

1998
1998
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(31 citation statements)
references
References 27 publications
1
29
0
1
Order By: Relevance
“…This is facilitated by the relatively noninvasive sampling and collection of sera and immune cells. Although this approach has been used successfully by toxicologists in the study of other systems [reviewed in (108)(109)(110)(111)(112)], a review of the literature reveals a paucity of studies dealing with neurotoxic exposures and autoimmune responses (113).…”
Section: Neurocytology Immunology and Immunoprivilegementioning
confidence: 99%
“…This is facilitated by the relatively noninvasive sampling and collection of sera and immune cells. Although this approach has been used successfully by toxicologists in the study of other systems [reviewed in (108)(109)(110)(111)(112)], a review of the literature reveals a paucity of studies dealing with neurotoxic exposures and autoimmune responses (113).…”
Section: Neurocytology Immunology and Immunoprivilegementioning
confidence: 99%
“…Although public health concerns about mercury exposures have generally focused on neurodevelopmental toxicity, mercury, particularly inorganic mercury (iHg), has been extensively studied in animal models for its immunotoxic properties, which include both autoimmunity and immunosuppression. The autoimmune effects of iHg in susceptible rodent strains include induction of specific autoantibodies, polyclonal activation of T and B cells, increased serum immunoglobulin G1 (IgG1) and IgE, cytokine dysregulation, and an immune complex glomerulonephritis (Bigazzi 1994;Griem and Gleichmann 1995;Mathieson 1992;Moszczynski 1997;Pollard and Hultman 1997).…”
mentioning
confidence: 99%
“…Mercury in high doses is a neurotoxin [7]. The experimental studies, mainly in animals, showed that mercury also affects the immune system by inducing lymphoproliferation and autoimmunity [2,4]. The salient features of the mercury-induced autoimmunity are the ANA and antilaminin antibodies [2,4].…”
Section: Resultsmentioning
confidence: 99%
“…These observations prompted us to examine the possibility of a potential relationship between mercury exposure and autoimmune response in autism. We hypothesized that if autism involved such a connection then autistic children should harbor elevated levels of mercuryinduced autoimmune markers, in particular the antinuclear antibodies (ANA) against nucleolar antigens and the antilaminin antibodies against basement-membrane-derived laminin protein [2,4]. We therefore profiled these two autoimmune markers in autistic and normal children.…”
Section: Introductionmentioning
confidence: 99%